How do we comprehend linguistic and visual narratives? A study in children with typical development. (September 2022) - Adornetti, Ines; Chiera, Alessandra; Altavilla, Daniela; Deriu, Valentina; Lecci, Camilla Maria; Marini, Andrea; Valeri, Giovanni; Magni, Rita; Ferretti, Francesco
Abstract: The present study investigated the comprehension of narrative with reference to global coherence, i.e., the global representation of story meaning and connectedness, across two different expressive modalities: stories conveyed through written language and stories conveyed through sequences of images. Two cognitive abilities possibly underpinning such comprehension were assessed: Central Coherence (CC) and Theory of Mind (ToM). Two groups of children with typical development aged between 8.00 and 10.11 years were included in the study: 40 participants received the narrative comprehension task in the linguistic modality; 40 participants were administered the narrative comprehension task in the visual condition. Analyses revealed that a change in the expressive code used to convey narratives did not entail a change in the overall comprehension performance: children of the two groups performed similarly on the narrative task. As for the cognitive abilities, CC and ToM scores were positively correlated with narrative comprehension score only in the visual narrative comprehension task, and not in the linguistic one. Moreover, a regression analysis showed that, along with age, CC significantly predicted the visual narrative comprehension score. The implications of these results are discussed. Highlights: This study explores the comprehension of linguistic and visual stories and its cognitive underpinnings in children. A first group received the narrative task in the writtenmodality; a second group in the visual condition. Children of the two groups equally understood narratives in the two modalities. The cognitive processes underpinning linguistic and visual narrative comprehension were different.